Host-status and host-sensitivity of hybrid sorghum-Sudan grass to tropical meloidogyne species and races and infection of the nematode-susceptible sweet potato from residual soil nematodes - Selapa, Vision Tabi (My University, 2021)
Worldwide, root-knot (Meloidogyne species) nematodes are considered to be the most important and damaging genus in crop husbandry. The existence of a wide host range, over 2000 plants, and several biological races, makes the management of this nematode genus difficult with nematode-resistant crop Hybrid Sorghum Sudan grass (Sorghum bicolor × Sorghum Sundanese) has been classified as being resistant to certain Meloidogyne species and races, with a wide range of uses in crop rotation intended to manage nematode population densities. However, due to the ability of nematodes to enter chemiobiosis when gradually exposed to chemicals, this hybrid might not be effective in managing nematode population densities for the subsequent highly susceptible sweet potato (Ipomoea batatas L.) cultivars. The objective of the study was to determine whether hybrid Sorghum-Sudan grass would suppress M. javanica (Trial 1), M. incognita race 2 (Trial 2) and M. incognita race 4 (Trial 3) population densities, allowing a nematode susceptible sweet potato cv. ′Beauregard′ as successor crop to be cultivated without suffering nematode damage. The hybrid Sorghum-Sudan grass study was conducted under greenhouse conditions, with seven inoculation levels, namely, 0; 5; 25; 125; 625; 3 125 and 15 625 eggs and second-stage juveniles (J2) of each nematode species or race, arranged in randomised complete block design, with six replications and validated in time. Plant growth, foliar nutrient elements and nematodes were collected at 56 days after inoculation and prepared for analysis using standard methods. The reproductive factor (RF) at all levels was zero, whereas nematode inoculation at all levels did not have any effect on plant growth of the hybrid Sorghum-Sudan grass. However, the nematode levels affected the accumulation of nutrient elements and the quality of forage. After cultivating the susceptible sweet potato cultivar in pots xxx previously with hybrid Sorghum-Sudan grass at increasing levels of M. javanica alone, that is in Trial 1, similar results were observed with respect to RF and lack of nematode damage to plant growth. Consequently, the hybrid was suitable for use in crop rotation with sweet potato for the purpose of managing nematode population densities of thermophilic Meloidogyne species and/or races.
Thesis (M. Sc. (Plant Protection)) -- University of Limpopo, 2021
Keywords: Root-knot; Nematodes; Crop husbandry; Meloidogyne species; Nematode-resistant crops; Soil pests; Root-knot nematodes; Hybrid sorghum; Crop rotation; Plant nematodes; Sudan grass; Sweet potatoes -- Diseases and pests